In vitro antioxidant, anti-inflammatory, anti-cancer and in silico molecular docking studies of Clerodendrum thomsoniae - Kar, Pallab; Oriola, Ayodeji O.; Oyedeji, Adebola O. (Journal of Phytology, 2024)
Clerodendrum thomsoniae is a member of the Lamiaceae family and is found throughout Asia, Australia, Africa, and America. C. thomsoniae (CT), mostly utilized in the floriculture sector, is sometimes referred to as bleeding heart vine or bag flower due to its exquisite decorative qualities. Apart from its high value in the floriculture industry, the plant has been utilized in traditional Indian and Japanese medicine to treat a variety of ailments. There is a dearth of information on the biological properties of the plant and its putative ingredients. Therefore, this study evaluated the antioxidant, anti-inflammatory, and anti-cancer potentials of the extract, as well as identified its phytocompounds. The antioxidant screening was based on nitric oxide (NO), hydrogen peroxide (H2O2), hydroxyl, and superoxide radical scavenging assays. In vitro anti-inflammatory activity of the extract was based on the egg albumin denaturation (EAD) assay, while the 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) cell viability assay was used to determine its anti-cancer potential. The chemical composition of the extract was determined using the hyphenated gas chromatography-mass spectrometry (GC-MS) method. Lastly, the identified phytocompounds were molecular docked against the inflammatory [NF-κβ (4DN5)] and cancer [mdm2 (3W69)] proteins. At 200 μg/mL, CT extract-treated Vero normal cells exhibited more viability (78.32±1.19%) than the one treated with the human renal adenocarcinoma (ACHN) cell line (33.45±0.66%), which suggests CT extract to be selectively cytotoxic to the cancer cells. The extract also demonstrated considerable inhibition of EAD (IC50=164.59±17.85 μg/mL). Thus, the observed anti-cancer and anti-inflammatory properties of CT extract may be attributed to its notable NO and H2O2 radicals scavenging activities, with IC50 values of 205.7±11.44 and 69.74±6.50 μg/mL respectively. GC-MS analysis of the extract revealed sixteen major compounds. In silico studies indicated α-tocopherol and stigmasterol as the most promising compounds, having exhibited the highest binding energy scores of -9.9 and -8.7 kcal/mol against NF-κβ (4DN5) and mdm2 (3W69) proteins respectively. In conclusion, C. thomsoniae leaf extract showed considerable antioxidant, anti-inflammatory, and anti-cancer properties, which may be attributed to its α-tocopherol and stigmasterol contents.